Development Of One-End Fault Location Algorithms For Power Distribution And Transmission Systems - Ngu, Eng Eng (2012)
The thesis concentrates on developing new and simple fault location algorithms for both power distribution and transmission systems. Accurate fault location on overhead transmission and distribution lines plays an important role in maintaining the reliability of a power system. In order to locate the fault accurately on power distribution and transmission lines,new one-end fault location algorithms are developed in this work.